Composite carbon material and application thereof
By preparing carbon composite materials containing thiol, ether bonds and carboxyl groups, the problems of sulfateization and low hydrogen evolution overpotential in the partially charged state of lead-acid batteries are solved, and the battery cycle life is extended and hydrogen precipitation is reduced.
Patent Information
- Application Number
- CN202311154364.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-08
AI Technical Summary
Lead-acid batteries are prone to sulfation problems and low overpotential overpotential of carbon materials under partially charged states, resulting in a shortening of the cycle life.
By preparing a new type of carbon composite material for lead-carbon batteries, sintered with thiol polyethylene glycol carboxylic acid and soluble lead salt to form a carbon composite material containing thiol, ether bonds and carboxy groups. The ether bonds form stable bonds with carbon and lead elements, improve the crystallization process of lead sulfate, and occupy the hydrogen evolution active site of the carbon material through C-O-Pb bonds and thiol groups to increase the hydrogen evolution overpotential.
It effectively improves the refinement of lead sulfate grains, extends the battery cycle life, reduces the precipitation of hydrogen, and reduces the consumption of electrolyte.
Abstract
Description
Technical Field
[0001] The present application relates to a composite carbon material and application thereof, belonging to the field of conductive materials. Background Art
[0002] As a relatively old energy storage technology, lead-acid batteries have a history of more than 160 years. Based on their low cost, high safety and high recycling rate, this type of battery is widely used in large-scale long-term energy storage or hybrid electric vehicles (HEV) and electric vehicles (EV). However, in the working environment of HEV and EV, lead-acid batteries usually work in a partial state of charge mode. This working condition will cause the negative electrode to accumulate large lead sulfate crystals that cannot be eliminated by simple means, and the negative electrode will be sulfated, which greatly reduces the cycle life of the battery. In order to improve the cycle life of lead-acid batteries in a partial state of charge, researchers have successfully developed an upgraded product, lead-carbon batteries, by adding highly conductive activated carbon to the negative electrode of lead-acid batteries. The addition of carbon materials can improve the problem of negative electrode sulfation to a certain extent, but the low hydrogen evolution overpotential of the carbon material itself brings a lot of hydrogen evolution problems to the battery. Summary of the invention
[0003] The present invention solves the battery sulfation problem and the problem of low hydrogen evolution overpotential of carbon materials by preparing a novel carbon composite material for lead-carbon batteries. The carbon composite material is prepared by blending and sintering mercapto polyethylene glycol carboxylic acid and soluble lead salt to obtain a carbon composite material containing mercapto, ether bonds and carboxyl groups. The CO bonds formed by the two ends of the ether bonds with the carbon element and the O-Pb bonds formed with the lead element are used to take the lead atom as the crystallization site, and the ether bonds and mercapto groups can produce a synergistic effect to improve the binding energy of lead ions and sulfate radicals, which can effectively improve the lead sulfate crystallization process, refine the lead sulfate grains, and extend the battery cycle life. In addition, a large number of CO-Pb bonds and mercapto groups can effectively occupy the hydrogen evolution active sites of the carbon material, improve the hydrogen evolution overpotential of the carbon material, reduce the amount of hydrogen precipitation during the use of the lead-carbon battery, reduce the consumption of the battery electrolyte, and further improve the cycle life of the lead-carbon battery.
[0004] According to one aspect of the present application, a composite carbon material is provided, characterized in that:
[0005] The composite carbon material is obtained by the following steps:
[0006] Mixing mercapto polyethylene glycol carboxylic acid with lead salt and sintering to obtain the composite carbon material;
[0007] The composite carbon material contains mercapto groups, ether bonds, CO bonds and C-Pb bonds;
[0008] In the composite carbon material, the mass content of the Pb element is 1 to 40 wt%, and the mass content of the O element is 1 to 40 wt%;
[0009] The specific surface area of the composite carbon material is 500 to 2500 m 2 / g;
[0010] The tap density of the composite carbon material is 1.2-3.0 g / cm 3 .
[0011] The molecular weight of the mercapto polyethylene glycol carboxylic acid is 500 to 50,000;
[0012] The lead salt is selected from at least one of lead nitrate, lead chloride and tetraethyl lead;
[0013] The mass ratio of the mercapto polyethylene glycol carboxylic acid to the lead salt is 10 to 0.1:1;
[0014] The mixing is performed by ball milling.
[0015] The sintering temperature is 500-1500°C;
[0016] The sintering time is 1 to 48 hours.
[0017] The sintering atmosphere is a mixed atmosphere containing hydrogen and inactive gas;
[0018] The inert gas is selected from at least one of nitrogen, helium and argon;
[0019] The flow ratio of the inert gas to the hydrogen is 100-0.01:1;
[0020] The ratio of the total mass of the mercapto polyethylene glycol carboxylic acid and the lead salt to the total volume of the gas passing through during the sintering process is 1g:0.001-200L.
[0021] According to another aspect of the present application, an electrode is provided, comprising the above-mentioned composite carbon material.
[0022] According to another aspect of the present application, a lead-acid battery is provided, comprising the above-mentioned electrode.
[0023] The beneficial effects of this application include:
[0024] The present invention solves the battery sulfation problem and the problem of low hydrogen evolution overpotential of carbon materials by preparing a novel carbon composite material for lead-carbon batteries. The carbon composite material is prepared by blending and sintering mercapto polyethylene glycol carboxylic acid and soluble lead salt to obtain a carbon composite material containing mercapto, ether bonds and carboxyl groups. The CO bonds formed by the two ends of the ether bonds with the carbon element and the O-Pb bonds formed with the lead element are used to take the lead atom as the crystallization site, and the ether bonds and mercapto groups can produce a synergistic effect to improve the binding energy of lead ions and sulfate radicals, which can effectively improve the lead sulfate crystallization process, refine the lead sulfate grains, and extend the battery cycle life. In addition, a large number of CO-Pb bonds and mercapto groups can effectively occupy the hydrogen evolution active sites of the carbon material, improve the hydrogen evolution overpotential of the carbon material, reduce the amount of hydrogen precipitation during the use of the lead-carbon battery, reduce the consumption of the battery electrolyte, and further improve the cycle life of the lead-carbon battery. DETAILED DESCRIPTION
[0025] The present invention is described in detail below with reference to embodiments.
[0026] Unless otherwise specified, the raw materials in the examples were purchased from commercial sources and used directly without further treatment; the instruments and equipment used were based on the parameters recommended by the manufacturer.
[0027] In the embodiment, the cycle life of the lead-carbon battery is tested using a Blue Electric charge and discharge tester and a Newway charge and discharge tester.
[0028] In the embodiments, the presence of thiol, ether bond -O-, CO bond and C-Pb bond in the carbon material and the mass proportion of atoms of each element in the tested sample are obtained by infrared testing (FT-IR) and X-ray photoelectron spectroscopy (XPS) testing, respectively.
[0029] Example 1
[0030] Step 1: Prepare the composite carbon material by the following method:
[0031] First, 10g of mercapto polyethylene glycol carboxylic acid with a molecular weight of 1000 and 10g of lead nitrate were fully mixed by high-speed ball milling, and then the mixed powder was transferred to a nitrogen and hydrogen mixture at 800 degrees Celsius for full sintering, wherein the flow ratio of nitrogen to hydrogen was 95:5, and the sintering time was 8 hours. The prepared carbon material contained mercapto, ether bond -O-, CO bond and C-Pb bond, and the atomic mass of the Pb element accounted for 20% of the total mass of the tested sample, and the atomic mass of the oxygen element accounted for 20% of the total mass of the tested sample. Its specific surface area was 1100m 2 / g, tap density is 1.6g / cm 3 .
[0032] Step 2: Prepare lead-carbon battery electrodes and lead-carbon batteries by the following method and conduct cycle stability and gas evolution tests:
[0033] 1) Preparation of negative electrode: (1) Premix 600g lead powder, 9g prepared carbon material, 8.4g barium sulfate, and 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm in a high-speed mixer, add 84g deionized water to the premixed powder while stirring, and continue stirring for 10 minutes to obtain lead paste; (2) Scrape the lead paste onto a metal lead grid with a size of 70mm long, 50mm wide, and 2mm thick, and cure and dry to obtain a lead-carbon battery negative electrode. The curing temperature is 40oC, the humidity is 80%, and the curing time is 20 hours; the drying temperature is 80oC, and the time is 24 hours;
[0034] 2) Preparation of the positive electrode: The positive electrode of the lead-acid battery is prepared according to the same process steps as the negative electrode preparation steps (1) and (2), except that no carbon material is added to the positive electrode;
[0035] 3) Preparation of lead-carbon battery: three positive plates and two negative plates are placed in parallel with each other in an alternating manner, and a colloidal PE separator for lead-carbon battery is placed between the positive plates and the negative plates, and two negative plates are welded in parallel and three positive plates are welded in parallel respectively. The total mass of positive active material of the lead-acid battery (the total mass of the lead paste on the three positive plates after drying) is 60.0g, and the total mass of positive active material refers to the total mass of the lead paste contained in the three positive plates welded in parallel. The total mass of negative active material (the total mass of the lead paste on the two negative plates after drying) is 52.9g, and the total mass of negative active material refers to the total mass of the lead paste contained in the two negative plates welded in parallel. The positive and negative electrode grids are conventional lead grids with dimensions of 70 mm long, 50 mm wide and 2 mm thick. The positive and negative electrodes are placed in a tightly assembled battery box with a length of 76 mm, a width of 40 mm and a height of 100 mm. 83 g of the sulfuric acid electrolyte prepared above with a mass concentration of 1.275 g / ml is injected into the battery box.
[0036] The battery was tested for life at room temperature. The test conditions were: 4.2A constant current discharge for 59 seconds, 18A discharge for 1 second, 6.3A current 2.3V constant current constant voltage charge for 60 seconds at 25°C. The charge and discharge conditions were cycled 3600 times, then left to stand for 40 hours, and then restarted after 40 hours. The termination condition of the life test was that the battery voltage dropped below 1.2V. The assembled internal hybrid battery can run 54631 cycles in the room temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the room temperature cycle life of the assembled lead-carbon battery can reach 7.6 times the life of traditional lead-acid batteries.
[0037] The battery was subjected to a room temperature gas evolution test, and the test method was as follows: the battery was fully sealed with laboratory-specific commercial paraffin, and then an air duct was inserted into the exhaust port of the battery, the end of the air duct located inside the battery passed through a rubber plug with a length of 5 mm, and the end of the air duct located outside the working electrode chamber was introduced into a device for testing the gas volume by a water displacement method, and the inner and outer surfaces of the rubber plug through which the air duct passed and various connections between the air duct and the commercial water displacement method gas volume test device were firmly sealed with commercial AB glue, in order to ensure that the gas generated by the battery end was completely introduced into the commercial water displacement method gas volume measurement device, and the gas volume generated by the battery end was collected by the device, and the gas production rate was calculated. During the test, the battery system was placed in a constant temperature environment of 25°C, and a constant voltage of 2.4V was applied to both ends of the battery for 48 hours. It was calculated that the gas production rate of the lead-carbon battery of the carbon material formula was 0.18ml / (wh·h).
[0038] Example 2
[0039] According to the requirements of Example 1, without changing other conditions, the amount of mercapto polyethylene glycol carboxylic acid added in step 1 was changed to 1g. After testing, the prepared carbon material contained mercapto, ether bond -O-, CO bond and C-Pb bond, and the atomic mass of the Pb element accounted for 30% of the total mass of the tested sample, and the atomic mass of the oxygen element accounted for 10% of the total mass of the tested sample. The specific surface area of the prepared carbon composite material was 1163m 2 / g, tap density is 2.2g / cm 3 The assembled internal hybrid battery can run 52256 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 7.3 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.17ml / (wh·h).
[0040] Example 3
[0041] According to the requirements of Example 1, without changing other conditions, the addition amount of mercapto polyethylene glycol carboxylic acid in step 1 was changed to 100 g. After testing, the prepared carbon material contained mercapto, ether bond -O-, CO bond and C-Pb bond, and the atomic mass of the Pb element accounted for 10% of the total mass of the tested sample, and the atomic mass of the oxygen element accounted for 40% of the total mass of the tested sample. The specific surface area of the prepared carbon composite material was 1043 m 2 / g, tap density is 2.5g / cm 3The assembled internal hybrid battery can run 56527 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 7.9 times that of the traditional lead-acid battery. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.27ml / (wh·h).
[0042] Example 4
[0043] According to the requirements of Example 1, without changing other conditions, the flow ratio of nitrogen to hydrogen in step 1 was replaced with 50:50. The prepared carbon material contained thiol, ether bond -O-, CO bond and C-Pb bond, and the atomic mass of the Pb element accounted for 10% of the total mass of the tested sample, and the atomic mass of the oxygen element accounted for 30% of the total mass of the tested sample. The specific surface area of the prepared carbon composite material was 1984m 2 / g, tap density is 2.9g / cm 3 The assembled internal hybrid battery can run 48150 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 6.7 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.20ml / (wh·h).
[0044] Example 5
[0045] According to the requirements of Example 1, without changing other conditions, the flow ratio of nitrogen to hydrogen in step 1 was replaced with 5:95. The prepared carbon material contained thiol, ether bond -O-, CO bond and C-Pb bond, and the atomic mass of the Pb element accounted for 5% of the total mass of the tested sample, and the atomic mass of the oxygen element accounted for 40% of the total mass of the tested sample. The specific surface area of the prepared carbon composite material was 1732m 2 / g, tap density is 1.8g / cm 3 The assembled internal hybrid battery can run 38777 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 5.4 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.25ml / (wh·h).
[0046] Example 6
[0047] According to the requirements of Example 1, without changing other conditions, the sintering temperature in step 1 was changed to 600 degrees Celsius. The prepared carbon material contained thiol, ether bond -O-, CO bond and C-Pb bond, and the atomic mass of the Pb element accounted for 25% of the total mass of the tested sample, and the atomic mass of the oxygen element accounted for 15% of the total mass of the tested sample. The specific surface area of the prepared carbon composite material was 1456m 2 / g, tap density is 2.8g / cm 3 The assembled internal hybrid battery can run 41948 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 5.8 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.21ml / (wh·h).
[0048] Example 7
[0049] According to the requirements of Example 1, without changing other conditions, the sintering temperature of step 1 was changed to 1100 degrees Celsius. The prepared carbon material contained thiol, ether bond -O-, CO bond and C-Pb bond, and the atomic mass of the Pb element accounted for 30% of the total mass of the tested sample, and the atomic mass of the oxygen element accounted for 20% of the total mass of the tested sample. The specific surface area of the prepared carbon composite material was 1873m 2 / g, tap density is 2.6g / cm 3 The assembled internal hybrid battery can run 25503 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 3.5 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.26ml / (wh·h).
[0050] Example 8
[0051] According to the requirements of Example 1, without changing other conditions, the mercapto polyethylene glycol carboxylic acid with a molecular weight of 1000 in step 1 is replaced by the mercapto polyethylene glycol carboxylic acid with the same mass and a molecular weight of 50000. The prepared carbon material contains mercapto, ether bond -O-, CO bond and C-Pb bond, and the atomic mass of the Pb element accounts for 25% of the total mass of the tested sample, and the atomic mass of the oxygen element accounts for 25% of the total mass of the tested sample. The specific surface area of the prepared carbon composite material is 1934m 2 / g, tap density is 1.9g / cm 3The assembled internal hybrid battery can run 26629 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 3.7 times that of the traditional lead-acid battery. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.29ml / (wh·h).
[0052] Comparative Example 1
[0053] Lead-acid battery: According to the requirements of Example 1, without changing other conditions, step 2 "1) Preparation of negative electrode: (1) Premix 600g lead powder, 9g prepared carbon material, 8.4g barium sulfate, and 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm in a high-speed mixer, add 84g deionized water to the premixed powder while stirring, and continue stirring for 10min to obtain lead paste;" was changed to (without adding any carbon material) "1) Preparation of negative electrode: (1) Premix 600g lead powder, 8.4g barium sulfate, and 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm in a high-speed mixer, add 84g deionized water to the premixed powder while stirring, and continue stirring for 10min to obtain lead paste;" without adding other steps, and the lead-acid battery was prepared. The assembled internal hybrid battery can run 7200 cycles in the normal temperature life test. Lead-acid batteries do not have hydrogen evolution problems, so gas generation rate testing is not performed.
[0054] Comparative Example 2
[0055] Lead-carbon battery: According to the requirements of Example 1, other conditions were not changed, and the composite carbon material was not prepared. A lead-carbon battery with a specific surface area of 1300 m 2 / g of activated carbon is used as a carbon material additive for lead-carbon batteries. The assembled internal hybrid battery can run 10,800 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.40ml / (wh·h).
[0056] Comparative Example 3
[0057] According to the requirements of Example 1, without changing other conditions, the amount of mercapto polyethylene glycol carboxylic acid added in step 1 is changed to 0.1g. The prepared carbon material contains mercapto, ether bond -O-, CO bond and C-Pb bond, but the atomic mass of the Pb element accounts for 80% of the total mass of the tested sample, and the atomic mass of the oxygen element accounts for 0.5% of the total mass of the tested sample. Since the proportion of the Pb element in the prepared carbon material is too high and the proportion of -O-bond is too low, a stable CO-Pb bond cannot be formed, and the Pb element cannot effectively inhibit the hydrogen evolution of the carbon material. The assembled internal hybrid battery can run 6452 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.51ml / (wh·h). The specific surface area of the prepared carbon composite material is 40m 2 / g, tap density is 1.2g / cm 3 .
[0058] Comparative Example 4
[0059] According to the requirements of Example 1, without changing other conditions, the mercapto polyethylene glycol carboxylic acid in step 1 is replaced with an equal mass of n-butanol. The prepared carbon material does not contain mercapto, ether bond -O-, CO bond and C-Pb bond, and cannot form a stable CO-Pb bond. The Pb element cannot effectively inhibit the hydrogen evolution of the carbon material. The assembled internal hybrid battery can run 5356 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.91ml / (wh·h). The specific surface area of the prepared carbon composite material is 500m 2 / g, tap density is 1.5g / cm 3 .
[0060] Comparative Example 5
[0061] According to the requirements of Example 1, without changing other conditions, the sintering temperature in step 1 was changed to 300 degrees Celsius. Since the sintering temperature was too low, the thermodynamic conditions for generating the target carbon material could not be reached and the battery test could not be completed.
[0062] Comparative Example 6
[0063] According to the requirements of Example 1, without changing other conditions, the sintering temperature of step 1 is changed to 2000 degrees Celsius. Due to the high sintering temperature, the degree of graphitization of the carbon material is low, and a large amount of metallic lead is reduced. The prepared carbon material contains thiol, ether bond -O-, CO bond and C-Pb bond, but the atomic mass of the Pb element accounts for 70% of the total mass of the tested sample, and the atomic mass of the oxygen element accounts for 0.5% of the total mass of the tested sample. Since the proportion of the Pb element in the prepared carbon material is too high and the proportion of -O-bond is too low, a stable CO-Pb bond cannot be formed, and the Pb element cannot effectively inhibit the hydrogen evolution of the carbon material. The assembled internal hybrid battery can run 2834 laps in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.93ml / (wh·h). The specific surface area of the prepared carbon composite material is 20m 2 / g, tap density is 1.7g / cm 3 .
[0064] Comparative Example 7
[0065] According to the requirements of Example 1, without changing other conditions, the mercapto polyethylene glycol carboxylic acid in step 1 is replaced by polyethylene glycol dicarboxylic acid of the same molecular weight. The prepared carbon material does not contain mercapto groups, but contains ether bonds -O-, CO bonds and C-Pb bonds. The atomic mass of the Pb element accounts for 30% of the total mass of the tested sample, and the atomic mass of the oxygen element accounts for 20% of the total mass of the tested sample. Since the prepared carbon material does not contain mercapto groups, the optimal effect of improving the crystallization of lead sulfate grains cannot be achieved. The assembled internal mixed battery can run 8528 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.49ml / (wh·h). The specific surface area of the prepared carbon composite material is 1200m 2 / g, tap density is 1.3g / cm 3 .
[0066] Comparative Example 8
[0067] According to the requirements of Example 1, without changing other conditions, the mercaptopolyethylene glycol carboxylic acid in step 1 is replaced with the same mass of mercaptoglycolic acid. The prepared carbon material does not contain ether bonds -O-, but contains mercapto, CO bonds and C-Pb bonds. The atomic mass of the Pb element accounts for 15% of the total mass of the tested sample, and the atomic mass of the oxygen element accounts for 15% of the total mass of the tested sample. Since the prepared carbon material does not contain ether bonds, the optimal effect of improving the crystallization of lead sulfate grains cannot be achieved. The assembled internal mixed battery can run 7963 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.54ml / (wh·h). The specific surface area of the prepared carbon composite material is 1200m 2 / g, tap density is 1.4g / cm 3 .
[0068] Comparative Example 9
[0069] According to the requirements of Example 1, without changing other conditions, the ball milling process of step 1 is changed to disperse the precursors of each reactant in an aqueous solution, and then sintering is performed after sufficient drying to prepare a carbon composite material. Due to the lack of ball milling process, although the prepared carbon material contains thiol, ether bond -O-, CO bond and C-Pb bond, the characteristic peak of the C-Pb bond is very weak, the atomic mass of the Pb element accounts for 0.5% of the total mass of the tested sample, and the atomic mass of the oxygen element accounts for 20% of the total mass of the tested sample. The best effect of improving the crystallization of lead sulfate grains cannot be achieved. The assembled internal mixed battery can run 9035 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.61ml / (wh·h). The specific surface area of the prepared carbon composite material is 1100m 2 / g, tap density is 1.1g / cm 3 .
[0070] By analyzing the experimental results of the above embodiments and comparative examples, it can be concluded that the prepared composite carbon material can achieve the best cycle life of the battery only when it has thiol, ether bond -O-, CO bond and C-Pb bond at the same time, and the bond strength of each bond is relatively strong.
[0071] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A composite carbon material, characterized in that: The composite carbon material is obtained by the following steps: Mixing mercapto polyethylene glycol carboxylic acid with lead salt and sintering to obtain the composite carbon material; The composite carbon material contains mercapto groups, ether bonds, CO bonds and C-Pb bonds; In the composite carbon material, the mass content of the Pb element is 1 to 40 wt%, and the mass content of the O element is 1 to 40 wt%; The specific surface area of the composite carbon material is 500 to 2500 m 2 / g; The tap density of the composite carbon material is 1.2-3.0 g / cm 3 .
2. The composite carbon material according to claim 1, characterized in that The molecular weight of the mercapto polyethylene glycol carboxylic acid is 500 to 50,000; The lead salt is selected from at least one of lead nitrate, lead chloride and tetraethyl lead; The mass ratio of the mercapto polyethylene glycol carboxylic acid to the lead salt is 10 to 0.1:1; The mixing is performed by ball milling.
3. The composite carbon material according to claim 1, characterized in that The sintering temperature is 500-1500°C; The sintering time is 1 to 48 hours.
4. The composite carbon material according to claim 1, characterized in that: The sintering atmosphere is a mixed atmosphere containing hydrogen and inactive gas; The inert gas is selected from at least one of nitrogen, helium and argon; The flow ratio of the inert gas to the hydrogen is 100-0.01:1; The ratio of the total mass of the mercapto polyethylene glycol carboxylic acid and the lead salt to the total volume of the gas passing through during the sintering process is 1g:0.001-200L.
5. An electrode, characterized in that: A composite carbon material comprising the composite carbon material according to any one of claims 1 to 4.
6. A lead-acid battery, characterized in that: Containing the electrode according to claim 5.
Citation Information
Patent Citations
Preparation method for lead-carbon composite material of lead acid battery and composite negative plate
CN104393250A
PSA ultrasensitive detection method based on fluorescent signal of gold nanorod core-quantum dot satellite-like nanostructure assembly
CN105548108A
Nanoparticle-based liver-targeting therapy
CN110167530A
Composite material, and preparation method and application thereof
CN112928246A
Negative electrode lead paste of lead-carbon storage battery and preparation method of negative electrode lead paste
CN116565159A